A comprehensive dataset for understanding immune dynamics in colorectal cancer(Mendeley Data). - Zahra Mokhtari; Elham Amjadi; Hamidreza Bolhasani; Zahra Faghih; Amirreza Dehghanian; Marzieh Rezaei (Data in Brief, 2025)
Colorectal cancer (CRC), the second most common cause of cancer death in the world, can be divided by the location of the primary tumor in the large intestine: right and left colon, and rectum. Based on the location, CRC shows different molecular characteristics, incidence, pathogenesis, and outcome. Considering the importance of immune components in tumor development, analysis of their interactive relationships with tumor cells in the tumor microenvironment (TME) has received more attention. In addition, routine prognosis systems such as TNM classification have low power to predict the clinical outcome of the disease. Accordingly, the identification of immune-related markers in TME might help to predict the prognosis and clinical outcome of the disease. This research aimed to provide a well-organized histopathological microscopy image dataset for best-scoring CRC. The images were taken from tumor tissue sections of patients with CRC, immunohistochemically stained with antibodies specific for CD3, CD8, CD45RO, PD-1, LAG-3, and Tim3. The markers were separately determined in the tumor's invasive margin and center. The dataset is named CRC-ICM and contains 1,756 images from 136 patients with CRC. It also contains comprehensive information on the clinicopathological characteristics of the patients, with a special focus on the tumor side (right and left). It includes an Excel file describing the patient’s demographic, anatomical features, and histopathological grade. The initial version of CRC-ICM is published on the Elsevier Mendeley dataset portal, and the latest version is accessible at: https://databiox.com.